Cognitive Absorption: Its Effect on Online Shopping App User Interest - Astra Prima Budiarti; Awisal Fasyni; Rizki Sri Lasmini (University of Merdeka Malang, 2022)
The purpose of this study is to analyze the role of cognitive absorption in affecting a user's desire to use online shopping application on a regular basis. The methodologies used in this investigation are quantitative method. Primary data were collected through delivering questionnaires to individuals who met the criteria. Users of e-commerce application like Tokopedia, Shopee, Bukalapak, Lazada, Blibli, and others make up the study's demographic. A total of 253 respondents was randomly sampled using the accidental sampling method. Structural Equation Model (SEM) analysis is used in this study. The findings of this study indicate that cognitive absorption did not affect continuance intention directly, but the indirect effect construct a significant relationship. The indirect effect is derived from the mediation of the variables of perceived usefulness and satisfaction.